Pendampingan Pendirian Rulen Biru: Rumah Literasi dan Bimbingan Belajar - Faradillah Siska Alfiani; Afro Tsuroiyah; Ela Koirunisa; Allinda Hamidah (Kifah: Jurnal Pengabdian Masyarakat, 2025)
This community service activity has an impact on increasing understanding of reading, writing and arithmetic and literacy in Miru Village. To improve understanding of calistung and literacy. The establishment of a tutoring house and literacy house needs consistent assistance so that children in Miru village continue to be enthusiastic about literacy and further increase their motivation to learn. This study uses the ABCD method. This method of service is used to develop an asset-based community. The researcher carried out this assistance because the interest in reading in Miru Village was previously low and there were still some children who could not understand calistung well. However, after the existence of this tutoring house and literacy house, children have increased their motivation to learn, and their enthusiasm for literacy.